DEVELOPMENT AND VALIDATION OF A HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) METHOD FOR DETERMINATION OF FIPRONIL AND PYRIPROXYFEN IN A VETERINARY PHARMACEUTICAL PRODUCT (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
In the present study, an analytical HPLC method was developed for the estimation of Fipronil, Pyriproxyfen, Benzyl alcohol, Butylhydroxyanisole (BHA) and Butylhydroxytoluene (BHT) and related substances from a veterinary pharmaceutical product. The method showed linearity in the range of 0.44-200% with a correlation coefficient of 0.99. The method was validated for different validation parameters such as: specificity (peak identification and interference study), precision, accuracy, linearity, robustness, limit of detection (LOD) and limit of quantitation (LOQ), stability of standard solutions and sample solution. The results were found to be within the acceptance limits as per ICH guidelines.